Cultural differences and cross-border venture capital syndication - Dai, Na; Nahata, Rajarishi (Journal of International Business Studies, 2016)
We examine cross-border syndication in investments led by foreign venture capitalists (VCs) focusing on the potential correlation between cultural differences and the formation of VC syndicates. Contrary to the risk-sharing motive, we find that a greater cultural disparity between the countries of investors and their companies is actually associated with smaller VC syndicates. This is driven largely by lesser local investor representation in foreign VC-led syndicates. However, certain cultural disparity-related syndication strategies, such as the involvement of locally experienced foreign VCs or syndicate members from culturally similar countries, are associated with greater presence of local VCs who provide valuable monitoring services. We further show that these culture-linked syndication approaches are significantly correlated with VC financing and monitoring strategies in cross-border investments and their eventual success.